Probing prodrug metabolism and reciprocal toxicity with an integrated and humanized multi-tissue organ-on-a-chip platform. (1st April 2020) - Rajan, Shiny Amala Priya; Aleman, Julio; Wan, MeiMei; Pourhabibi Zarandi, Nima; Nzou, Goodwell; Murphy, Sean; Bishop, Colin E.; Sadri-Ardekani, Hooman; Shupe, Tom; Atala, Anthony; Hall, Adam R.; Skardal, Aleksander
Abstract: Current drug development techniques are expensive and inefficient, partially due to the use of preclinical models that do not accurately recapitulate in vivo drug efficacy and cytotoxicity. To address this challenge, we report on an integrated, in vitro multi-organoid system that enables parallel assessment of drug efficiency and toxicity on multiple 3D tissue organoids. Built in a low-cost, adhesive film-based microfluidic device, these miniaturized structures require less than 200 µL fluid volume and are amenable to both matrix-based 3D cell culture and spheroid aggregate integration, each supported with an in situ photocrosslinkable hyaluronic acid hydrogel. Here, we demonstrate this technology first with a three-organoid device consisting of liver, cardiac, and lung constructs. We show that these multiple tissue types can be kept in common circulation with high viability for 21 days and validate the platform by investigating liver metabolism of the prodrug capecitabine into 5-fluorouracil (5-FU) and observing downstream toxicity in lung and cardiac organoids. Then we expand the integrated system to accommodate six humanized constructs, including liver, cardiac, lung, endothelium, brain, and testes organoids. Following a 14-day incubation in common media, we demonstrate multi-tissue interactions by metabolizing the alkylating prodrug ifosfamide in the liver organoid to produce chloroacetaldehyde and induce downstream neurotoxicity. Our results establish an expandable, multi-organoid body-on-a-chip system that can be fabricated easily and used for the accurate characterization of drug interactions in vitro . Statement of Significance: The use of 3-dimensional (3D) in vitro models in drug development has advanced over the past decade. However, with several exceptions, the majority of research studies using 3D in vitro models, such as organoids, employ single tissue types, in isolated environments with no "communication" between different tissues. This is a significant limiting factor because in the human body there is significant signaling between different cells, tissues, and organs. Here we employ a low-cost, adhesive film-based microfluidic device approach, paired with a versatile extracellular matrix-derived hyaluronic acid hydrogel to support integrated systems of 3 and 6 3D organoid and cell constructs. Moreover, we demonstrate an integrated response to drugs, in which downstream toxicity is dependent on the presence of liver organoids. Graphical abstract: Image, graphical abstract